Risk Management in Credit Portfolios Concentration Risk and Basel II - Hibbeln, Martin; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2010)
Risk concentrations play a crucial role for the survival of individual banks and for the stability of the whole banking system. Thus, it is important from an economical and a regulatory perspective to properly measure and manage these concentrations. In this book, the impact of credit concentrations on portfolio risk is analyzed for different portfolio types and it is determined, in which cases the influence of concentration risk has to be taken into account. Furthermore, some models for the measurement of concentration risk are modified to be consistent with Basel II and their performance is compared. Beyond that, this book integrates economical and regulatory aspects of concentration risk and seeks to provide a systematic way to get familiar with the topic of concentration risk from the basics of credit risk modeling to present research in the measurement and management of credit risk concentrations.
Credit Risk Measurement in the Context of Basel II -- Concentration Risk in Credit Portfolios and Its Treatment Under Basel II -- Model-Based Measurement of Name Concentration Risk in Credit Portfolios -- Model-Based Measurement of Sector Concentration Risk in Credit Portfolios -- Conclusion.
Keywords: Economics; Finance; Economics/Management Science; Finance/Investment/Banking.; Financial Economics; Quantitative Finance